2021
DOI: 10.3390/cells10050991
|View full text |Cite
|
Sign up to set email alerts
|

Role of SNAREs in Neurodegenerative Diseases

Abstract: Neurodegenerative diseases are pathologies of the central and peripheral nervous systems characterized by loss of brain functions and problems in movement which occur due to the slow and progressive degeneration of cellular elements. Several neurodegenerative diseases are known such as Alzheimer’s disease, Parkinson’s disease and amyotrophic lateral sclerosis and many studies on the molecular mechanisms underlying these pathologies have been conducted. Altered functions of some key proteins and the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 113 publications
0
32
0
Order By: Relevance
“…This experimental study found that after Radix Rhei Et Rhizome treatment, its expression was significantly increased compared with the model group, indicating that Radix Rhei Et Rhizome may resist synapse damage or promote synaptic regeneration after cerebral ischemia. Synapse protein I gene (SYN1) mainly mediates the delivery of synaptic vesicles and circulation [ 73 ] and plays an important role in neurodegenerative diseases [ 74 ], such as Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis. This study suggests that SYN1 may be a potential drug target for neurodegenerative diseases caused by CI, among which Radix Rhei Et Rhizome can reduce CI by interfering with SYN1.…”
Section: Resultsmentioning
confidence: 99%
“…This experimental study found that after Radix Rhei Et Rhizome treatment, its expression was significantly increased compared with the model group, indicating that Radix Rhei Et Rhizome may resist synapse damage or promote synaptic regeneration after cerebral ischemia. Synapse protein I gene (SYN1) mainly mediates the delivery of synaptic vesicles and circulation [ 73 ] and plays an important role in neurodegenerative diseases [ 74 ], such as Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis. This study suggests that SYN1 may be a potential drug target for neurodegenerative diseases caused by CI, among which Radix Rhei Et Rhizome can reduce CI by interfering with SYN1.…”
Section: Resultsmentioning
confidence: 99%
“…The top 10 KEGG pathways (those enriched in the shortest paths) are shown in Table 6 ( Turi et al, 2019 ; Jia et al, 2021 ; Chothani et al, 2019 ; Yin et al, 2021 ; Manhas and Rath, 2020 ; Li et al, 2018 ; Nakajima et al, 2019 ; Hosseini et al, 2021 ; Critchley et al, 2018 ; Lathe et al, 2014 ; Margiotta, 2021 ; Nickel et al, 2002 ; Chen et al, 2020 ; Luo et al, 2020 ; Miller et al, 2021 ; Stadtman et al, 2005 ; Bonifácio et al, 2021 ; Blachier et al, 2020 ; Kumar et al, 2017 ; Récher, 2021 ; Klemm and Ruland, 2006 ). The most frequently enriched KEGG pathway was “ribosome” (enriched in eight shortest paths; Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…The top enriched KEGG pathway (with the minimum FDR) was “SNARE interactions in vesicular transport” ( p = 4.6346 and FDR = 0.0086; Figure 4B ). The SNARE protein is an essential component in the regulation of vesicle fusion and plays a key part in maintaining cell homeostasis ( Margiotta, 2021 ). Vesicle transport is the main mechanism of protein and lipid exchange between membrane-bound organelles in eukaryotic cells ( Nickel et al, 2002 ); vesicle transport in mitochondria also affects mitochondrial function, which is one of the key characteristics of aging ( Chen et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the SNARE complex is vital in the formation of vesicle fusion, vesicle recycling and neurotransmitter release. The defects in the formation of the SNARE complex, SNARE-dependent exocytosis, and SNARE-mediated vesicle fusion are associated with neurological diseases 80 .…”
Section: Discussionmentioning
confidence: 99%